Kebijakan Moneter dalam Ekonomi Islam - Laila Fauzila Zahera; Rusmitha Devy; Vivi Meilani (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
Monetary policy in Islamic economics is an important aspect in maintaining economic stability and promoting the welfare of the people. In the Islamic economic paradigm, monetary policy aims to create a balance between sustainable economic growth and fair distribution of wealth. Principles such as fairness, sustainability and fairness are the basis for formulating monetary policy. First, monetary policy must ensure that the creation of new money is carried out responsibly, avoiding inflation that is detrimental to society. In addition, the Islamic monetary system encourages the use of financial instruments based on sharia principles, such as mudharabah and musyarakah, which encourage healthy economic participation. Second, monetary policy must pay attention to aspects of wealth redistribution to reduce economic inequality. This can be achieved through collecting zakat, infaq and sadaqah as well as channeling funds to sectors in need, such as education, health and poverty alleviation. By implementing monetary policy in accordance with Islamic economic principles, it is hoped that an economy that is inclusive, sustainable and fair can be realized for all members of society.